Ventricular inversion without transposition of the great vessels in situs inversus - Espino-Vela, Jorge (1970)
A classification of one type of congenital malformation previously reported (de la Cruz et al., 1967) is based on the integration of an embryological theory for ventricular inversions with the embryological concepts of trunco-conal malformations (de la Cruz and da Rocha, 1956). In that classification we consider that in each situs, either solitus or inversus ventricular inversions may be associated with: (a) normally arranged great vessels (not transposed); (b) transposition of the great vessels; (c) persistent truncus arteriosus. The patients had ventricular inversion without transposition of the great vessels in situs inversus. The correct anatomical diagnosis was not foreseen but the physiopathological diagnosis was correct: pulmonary ischaemia associated with septal defects. In one case these facts were substantiated by catheterization and by angiocardiographic findings which led us to advise surgery. Haemodynamically isolated inversion of the ventricles is as severe a malformation as complete (not corrected) transposition of the great vessels. However, an operation of the anastomotic type between a systemic vessel and the narrow pulmonary artery seemed justified in these cases, as a means to convey more blood to the lungs and improve the saturation of the arterial blood. It was unsuccessfully carried out in one patient. The anatomical, radiological, and electrocardiographic features which might aid in the diagnosis are analysed.